2019
DOI: 10.1021/acssensors.9b00275
|View full text |Cite
|
Sign up to set email alerts
|

Easy Diagnosis of Jaundice: A Smartphone-Based Nanosensor Bioplatform Using Photoluminescent Bacterial Nanopaper for Point-of-Care Diagnosis of Hyperbilirubinemia

Abstract: One of the concerns of parents in the first days of their baby's birth is the baby's risk of jaundice/ hyperbilirubinemia. This is because more than 60% of babies are born with jaundice that, if not timely diagnosed and subsequently treated, can lead to serious damage to their health. On the other hand, despite recent progress in sensor technology for clinical applications, the development of easy-to-use, cost-effective, sensitive, specific, and portable diagnostic devices, which use nontoxic and biodegradable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 51 publications
2
57
0
Order By: Relevance
“…Since the conductivity of the BC is extremely low, the frequency shift caused by the acoustoelectric effect was calculated to be only ~1. 16 Hz when the RH value was changed from 30% to 93%. The resistance value of R0 at 30% RH shown in Fig.…”
Section: Sensing Measurement Results and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the conductivity of the BC is extremely low, the frequency shift caused by the acoustoelectric effect was calculated to be only ~1. 16 Hz when the RH value was changed from 30% to 93%. The resistance value of R0 at 30% RH shown in Fig.…”
Section: Sensing Measurement Results and Mechanismsmentioning
confidence: 99%
“…For example, Tang et al [12] reported a SAW humidity sensor on the ST-cut quartz substrate, exhibiting both good thermal stability and sensitivity. Bacterial cellulose (BC) is one of the emerging functional nanomaterials with important applications in biotechnology and materials science [13][14][15][16]. It is a filamentous and fibrous byproduct secreted by microorganisms such as acetobacters and agrobacteria [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A dark chamber, as seen in Figure S13, with well-defined places for smartphone camera and UV/white lamps was fabricated using a 3D printer 34 . Two UV LED slight modifications of the method described by Liu et al [64][65] .…”
Section: Fabrication Of 3d-printed Smartphone-based Sensing Setupmentioning
confidence: 99%
“…We have already fabricated optical sensing platforms using bacterial cellulose (BC) nanopaper [31][32][33][34] . In the current research, the optical sensing platforms were fabricated from ChNF paper.…”
Section: Introductionmentioning
confidence: 99%
“…Tabatabaee et al, 2019, have prepared a photo lumines cent nano paper-based biosensor for early diagnosis of jaundice through the detection of Bilirubin in infants’ blood samples. This provides an easy, effective, non-toxic, disposable, and inexpensive biosensor with a smartphone readout [ 88 ]. Smartphone readout systems provide great potential for point-of-care and point-of-need platforms [ 89 ].…”
Section: Biosensors For Detection Of Macromoleculesmentioning
confidence: 99%